Native American Languages and Literacy: Issues of Orthography Choice and Bilingual Education - Biava, Christina (Kansas Working Papers in Linguistics, 1990)
Native American language communities have had four choices regarding the adoption or change of a writing system in recent years: to adopt or not to adopt a system, or in the case of an existing system, to alter it or not to alter it. Also examined are criteria of orthography choice and functions of literacy. Bilingual education issues are seen as the most important function of Native language literacies. Also examined are problems that face Native language literacy programs.